(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
Interaction of thiocyanate complex of palladium (II) with triphenyl raw organic basic dye fucsine in sulfuric acid environment has been studied. The optimal conditions for the formation of ionic associate (IA) and its extraction in organic phase, also concentration of dye, the range of palladium (II) content selectivity of extraction are determined. The content of IA is determined.